2016
DOI: 10.1002/elan.201600270
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review on Hydrogen Evolution Electrocatalysis: Re‐exploring the Volcano‐relationship

Abstract: The "volcano"-relationship for the electrocatalytic hydrogen evolution reaction seems to be a generally accepted phenomenology in electrochemistry. Based on the Sabatier principle, which suggests a not too strong, nor too weak binding of reaction intermediates as prerequisite for high reaction rates, it provides a straightforward and intuitive explanation for a plethora of experimental results. However, while the Sabatier principle as a main paradigm of heterogeneous catalysis was never really disputed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
227
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 270 publications
(255 citation statements)
references
References 62 publications
14
227
0
2
Order By: Relevance
“…In the literature, commonly, conventional volcano analyses are used to comprehend activity trends in a homologous series of materials . Despite of the success of the volcano approach in the field of electrocatalysis, critical voices are heard: it has been reported that the simple Volcano picture, relying on binding energies only, does not describe activity trends always correctly . This finding is directly visible when assessing activity trends of RuO 2 (110) or IrO 2 (110) in the CER or OER, based on ab initio studies, from the literature.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, commonly, conventional volcano analyses are used to comprehend activity trends in a homologous series of materials . Despite of the success of the volcano approach in the field of electrocatalysis, critical voices are heard: it has been reported that the simple Volcano picture, relying on binding energies only, does not describe activity trends always correctly . This finding is directly visible when assessing activity trends of RuO 2 (110) or IrO 2 (110) in the CER or OER, based on ab initio studies, from the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Although oxygen can be considered a useless by‐product in artificial photosynthesis, water oxidation provides the reducing equivalents necessary for the synthesis of fuels, typically by reduction of protons to hydrogen, or by reduction of carbon dioxide to carbon monoxide, formic acid, methanol or methane . Efforts in this field have been focused on the development of new and efficient catalysts, but also on the mechanistic investigation for the identification of reaction rates and intermediates involved in breaking and formation of bonds, in particular the most challenging one related to the formation of the oxygen–oxygen bond , …”
Section: Introductionmentioning
confidence: 99%
“…11 In this article we address the overpotential of hydrogen evolution on the Cu(111) electrode. To do this, we employ theoretically calculated Gibbs energies, which are equal to the internal energies plus p V and T S contributions.…”
mentioning
confidence: 99%
“…10 The multitude of variables that affect the exchange current densities used in volcano plots continue to be explored. 11 In this article we address the overpotential of hydrogen evolution on the Cu(111) electrode. To do this, we employ theoretically calculated Gibbs energies, which are equal to the internal energies plus p V and T S contributions.…”
mentioning
confidence: 99%